Processing and acquisition of temporality in L2 Mandarin Chinese: Effects of grammatical and lexical aspects - Fang, Shaohua; Xu, Yi (Frontiers in Psychology, 2022)
This study investigated the second language (L2) processing and acquisition of Chinese temporality, specifically the interaction of grammatical and lexical aspects. An experimental group of 31 English-speaking learners of Chinese and a control group of 29 native speakers of Mandarin Chinese completed an online sentence-picture matching task and an offline translation task. Results from these experiments demonstrated the prototype effect: in aspectual development, perfective aspect started with telic verbs and progressive aspect started with activity verbs, in accordance with the Aspect Hypothesis, both for online processing and offline comprehension. The prototype effect of the grammatical aspect was evident for activity verbs but less so for accomplishment verbs in the L2 group across tasks, and this was explained through language-specific properties and L2 learners' instructional input. In addition, L2 proficiency and working memory capacity were found to modulate these processes.